Evaluating Weathering of Food Packaging Polyethylene-Nano-clay Composites: Release of Nanoparticles and their Impacts - Han, Changseok (NanoImpact, 2018)
Nano-fillers are increasingly incorporated into polymeric materials to improve the mechanical, barrier or other matrix properties of nanocomposites used for consumer and industrial applications. However, over the life cycle, these nanocomposites could degrade due to exposure to environmental conditions, resulting in the release of embedded nanomaterials from the polymer matrix into the environment. This paper presents a rigorous study on the degradation and the release of nanomaterials from food packaging composites. Films of nano-clay-loaded low-density polyethylene (LDPE) composite for food packaging applications were prepared with the spherilene technology and exposed to accelerated weathering of ultraviolet (UV) irradiation or low concentration of ozone at 40 °C. The changes in the structural, surface morphology, chemical and physical properties of the films during accelerated weathering were investigated. Qualitative and quantitative changes in properties of pristine and aged materials and the release of nano-clay proceeded slowly until 130 hr irradiation and then accelerated afterward resulting complete degradation. Although nano-clay increased the stability of LDPE and improved thermal and barrier properties, they accelerated the UV oxidation of LDPE. With increasing exposure to UV, the surface roughness, chemiluminescence index, and carbonyl index of the samples increased while decreasing the intensity of the wide-angle X-ray diffraction pattern. Nano-clay particles with sizes ranging from 2–8 nm were released from UV and ozone weathered composite. The concentrations of released nanoparticles increased with an increase in aging time. Various toxicity tests, including reactive oxygen species generation and cell activity/viability were also performed on the released nano-clay and clay polymer. The released nano-clays basically did not show toxicity. Our combined results demonstrated the degradation properties of nano-clay particle-embedded LDPE composites toxicity of released nano-clay particles to A594 adenocarcinomic human alveolar basal epithelial cells was observed, which will help with future risk based-formulations of exposure.